Current state and prospects of nano-delivery systems for sorafenib. Issue 18 (12th December 2018) - Khan, Muhammad Adeeb; Raza, Abida; Ovais, Muhammad; Sohail, Muhammad Farhan; Ali, Shaukat
ABSTRACT: Sorafenib is the only approved targeted agent against hepatocellular carcinoma (HCC). It has several limitations predominantly poor aqueous solubility and hepatic first-pass effect that limits its oral delivery leading to low bioavailability, large inter-subject variability, narrow therapeutic window and side effects. Tosylate is used to improve its solubility, which is practically insoluble in water (60 µg/mL) so problems with sorafenib solubility persist. To improve the paharmacokinetic profile, minimize the side effects, and targeting drug to the tumor tissues, several polymeric nano-formulations are being evaluated. In this comprehensive review, various reported polymeric nano-delivery systems for sorafenib are comprehensively covered. GRAPHICAL ABSTRACT: